2012
DOI: 10.1002/cbic.201200426
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Soluble Form of Human CD73 with Ecto‐5′‐Nucleotidase Activity

Abstract: CD73 is a dimeric ecto-5'-nucleotidase that is expressed on the exterior side of the plasma membrane. CD73 has important regulatory functions in the extracellular metabolism of certain nucleoside monophosphates, in particular adenosine monophosphate, and has been linked to a number of pathological conditions such as cancer and myocardial ischaemia. Here, we present the crystal structure of a soluble form of human soluble CD73 (sCD73) at 2.2 Å resolution, a truncated form of CD73 that retains ecto-5'-nucleotida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…Identified residues for phosphate binding (Asn-99 and Arg-392) and the predicted catalytic dyad residue His-100 were found to be critical for AMP hydrolysis. This suggests that the enzymatic mechanism is similar to what has been described for CD73 and E. coli 5Ј-nucleotidase (32,33).…”
Section: Volume 290 • Number 52 • December 25 2015supporting
confidence: 58%
See 1 more Smart Citation
“…Identified residues for phosphate binding (Asn-99 and Arg-392) and the predicted catalytic dyad residue His-100 were found to be critical for AMP hydrolysis. This suggests that the enzymatic mechanism is similar to what has been described for CD73 and E. coli 5Ј-nucleotidase (32,33).…”
Section: Volume 290 • Number 52 • December 25 2015supporting
confidence: 58%
“…In contrast, CD73 has been described as a zinc-dependent 5Ј-nucleosidase due to the fact that after stripping metal ions by EDTA treatment, Zn 2ϩ reconstitution resulted in the highest enzymatic activity when compared with other divalent cations. Furthermore, it was shown that CD73 is inactive with Mg 2ϩ as metal cofactor (32). Notably, the Zn 2ϩ concentration in human blood is ϳ6.2 mg/liter (ϳ0.1 mM) (42), which would allow optimal S5nA activity.…”
Section: Volume 290 • Number 52 • December 25 2015mentioning
confidence: 99%
“…1A) and finally by 59-nucleotidase for the conversion to adenosine, which acts at its own set of four GPCRs. Recently, the structures of 59-nucleotidase and ecto-nucleoside triphosphate diphosphohydrolase (CD39) were determined using X-ray crystallography (Heuts et al, 2012;Zimmermann et al, 2012). The structures of some of the other enzymes involved in processing purine receptor ligands, such as ecto-nucleotide pyrophosphatase/phosphodiesterase-1, have also been determined (Jansen et al, 2012).…”
Section: Medicinal Chemistry Of P2yrs: Focus On Nucleotidesmentioning
confidence: 99%
“…Ecto-5'-nucleotidase is a dimeric extracellular glycoprotein with similar open and closed conformations to bacterial enzymes [121]. A crystal structure of the closed and open formations of human e'5NT have been obtained [174,175]. Structural control of the domain movement may be responsible for the selectivity of monophosphate nucleotides [176].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%